(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
Sugarcane is the raw material for sugar. Limited availability of planting materials has led to a decline in sugar production. The development of synthetic sugarcane seeds offers an alternative for large-scale propagation with long-term storage. This study aims to evaluate the effect of BAP and osmotic regulators on the germination and storage capacity of synthetic sugarcane seeds. The synthetic seeds were produced using the encapsulation technique, whereby basal shoots of the NXI 1-3 sugarcane variety were inserted into 3% sodium alginate and treated with various concentrations of BAP (0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm, 2 ppm), mannitol (0%, 1%, 2%, 3%), and PEG (0%, 1%, 2%, 3%) and then dripped into a 100 mM CaCl2. The results showed that BAP at a concentration of 1.5 ppm provided the best response, with the fastest germination time (4.6 days) and the highest germination percentage (100%). Among the osmotic regulators, 3% mannitol produced the longest germination time (21.75 days), with seed viability of 85% and germination percentage of 60%, demonstrating its effectiveness in extending seed storage life. BAP increases seed viability and growth performance, while mannitol effectively maintains seed dormancy so that it can be used to maintain sugarcane seed availability. This study also supports the achievement of the SDGs, particularly SDG 2 (Zero Hunger) through increased seed production to ensure sugarcane seed availability, and SDG 9 (Industry, Innovation, and Infrastructure) through the application of encapsulation methods as a biotechnology innovation to increase seed production.